The Influence of Proportion Dominance and Global Need Perception on Donations - Ein-Gar, Danit; Give’on, Amir (Frontiers in Psychology, 2022)
Many donation-raising platforms request that first-time donors choose the charitable causes they most care about so that future campaign recommendations can best match donors’ charitable preferences. While matching charitable campaigns to donors’ reported preferences has its benefits, little is known about other effects that choosing charitable causes may evoke. We focus on how choosing charitable causes influences charitable behavior. We find two effects of the number of charitable causes donors choose on their subsequent charitable behavior. In studies 1 and 2, we show that a reference number of the maximum charitable causes donors can choose has a negative effect on charitable behavior. A small (versus large) reference number yields a greater likelihood to donate and a higher donation amount. This effect is aligned with the proportion dominance rationalization. In studies 3 and 4, we show that the number of charitable causes donors voluntarily choose as important to them is positively associated with subsequent charitable behavior. This association is mediated by global need perception. As the number of causes donors choose increases, donors experience an escalation in their perception of global neediness, which in turn motivates their willingness to donate and the donation amount. In Study 5, we show how the two effects together shape charitable behavior. These effects are observed while controlling the donors’ inherent prosocial attitudes toward help giving. With more than 1.5 million registered non-profit organizations operating in the United States (National Center for Charitable Statistics, 2019), it has become almost impossible for donors to easily choose which charitable campaigns to support. Online charitable fundraising platforms (e.g., One Today by Google, Round Up, and Charity Miles), websites (e.g., AmazonSmile) and crowdfunding platforms (e.g., Fundly, JustGiving, and GoFundMe) try to ease donors’ search and decision processes by offering them personalized charitable options. First-time donors are asked to indicate the charitable causes they care most about, and then asked to donate to charitable campaigns that best match their preferences. Interestingly, little is known about how this initial stage of choosing charitable causes influences subsequent donation behavior. In this research, we ask how choosing the charitable causes one cares most about influences subsequent response to a charitable appeal. Obviously, the mere selection of preferred causes enables charities to offer personalized campaigns and create a better fit between non-profits and donors, which has a generally positive effect on charitable giving. However, in this research we focus on an overlooked aspect of these practices. We examine how the number of charitable causes donors indicate as important to them influences their donation giving. We test two opposite effects: the proportion dominance effect, an effect driven by prior research, and the global need perception effect, a new effect identified in this article. Both effects are driven by the number of causes donors choose.